(untitled) (Research, Society and Development, 2020)
This article is concerned to some reflections on the concepts of art education and human emancipation. To this aim, we consider the teaching of Arts in Basic Education according to the Law of Guidelines and Bases 9.394/96, the Law 13.278/16 and the challenges presented in this teaching-learning. It is a Bibliographic research, which consists of relating the thoughts of two authors: the conceptions of art education in Duarte Jr. (2010, 2012) and the concepts of “bancárias” practices in education, “Ser Mais”, human emancipation and autonomy in Paulo Freire (1996, 2011). Aiming to find similarities in the studies of the aforementioned authors on teaching practices and ways to encourage students’ autonomy. It is concluded that art education promotes autonomy, by respecting subjectivity and creating teaching-learning practices that comprehend the human being in an integral way. The body is also considered important in the learning process, not only the mind. Therefore, emotions and life experiences are welcomed.